1993
DOI: 10.1002/syn.890140409
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the dopaminergic receptor system after chronic administration of cocaine

Abstract: Several studies suggest that one of the most important factors contributing to cocaine dependence is an alteration in the actions of the neurotransmitter dopamine in the central nervous system. In order to understand some of the neuroreceptor consequences of cocaine administration, groups of rats were injected with cocaine (2 daily doses of 15 mg/kg) for 1 to 21 days. Binding of [3H]cocaine, [3H]SCH23390, [3H]raclopride, and [3H]BTCP in striatal and cortical tissue from the treated animals was compared to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 43 publications
5
32
0
1
Order By: Relevance
“…Similarly, the 6-h access rats that exhibited neither a sensitized locomotor response nor an elevated c-Fos reactivity to cocaine, also exhibited no change in DAT density. These results are also consistent with the data of Alburges et al, (1993;using [3H]BTCP) and of Claye et al, (1995;using [3H] GBR-12935) who showed increased levels of DAT in the nucleus accumbens or striatum of rats receiving a cocaine treatment regimen previously shown to resulting behavioral sensitization. Finally, the current results are consistent with the data of Letchworth et al, (2001;[3H]WIN35,428) showing increased DAT density in the N.Acc of rhesus monkeys self-administering cocaine in a pattern resembling recreational drug use in humans.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, the 6-h access rats that exhibited neither a sensitized locomotor response nor an elevated c-Fos reactivity to cocaine, also exhibited no change in DAT density. These results are also consistent with the data of Alburges et al, (1993;using [3H]BTCP) and of Claye et al, (1995;using [3H] GBR-12935) who showed increased levels of DAT in the nucleus accumbens or striatum of rats receiving a cocaine treatment regimen previously shown to resulting behavioral sensitization. Finally, the current results are consistent with the data of Letchworth et al, (2001;[3H]WIN35,428) showing increased DAT density in the N.Acc of rhesus monkeys self-administering cocaine in a pattern resembling recreational drug use in humans.…”
Section: Discussionsupporting
confidence: 91%
“…Whether this decreased D 2 receptor expression represents a vulnerability factor or a consequence of long-term cocaine exposure cannot be determined from these studies. Rodent studies investigating the long-term effects of cocaine exposure on D 2 receptor density have yielded inconsistent findings: studies have reported unchanged (Dwoskin et al, 1988;Alburges et al, 1993;Neisewander et al, 1994;Claye et al, 1995), increased (Taylor et al, 1979;Trulson and Ulissey, 1987;Zeigler et al, 1991) and decreased (Goeders and Kuhar, 1987;Kleven et al, 1990) D 2 receptor densities in the striatum. Studies in nonhuman primates are less numerous, but more consistent.…”
Section: Receptor Availability and Cocaine Dependencementioning
confidence: 99%
“…Studies have variously reported receptor downregulation (Maggos et al, 1998;Zeigler et al, 1991), upregulation (Alburges et al, 1992(Alburges et al, , 1993Macedo et al, 2004), and no alterations (Mayfield et al, 1992;Sousa et al, 1999) in D 1 densities between days 1 and 30 of withdrawal. Similar inconsistencies are reported with respect to D 2 receptors (upregulation (Macedo et al, 2004;Sousa et al, 1999;Zeigler et al, 1991); downregulation (Maggos et al, 1998;Volkow et al, 1993); no change (Alburges et al, 1992(Alburges et al, , 1993Maggos et al, 1998)). Given the complex interplay between mesostriatal ACh and DA described earlier, it is perhaps not surprising that the extant literature is inconsistent with respect to the direction of striatal cholinergic change resulting from, or effecting, cocaine administration.…”
Section: Neuroadaptation Ach Receptor Alterations Following Cocainementioning
confidence: 99%